Multi-user detection for the downlink of NOMA systems with multi-antenna schemes and power-efficient amplifiers - Ribeiro, F.; Ribeiro, F.; Guerreiro, J.; Guerreiro, J.; R. Dinis; Cercas, F.; D. Jayakody (Physical Communication, 2019)
Non-orthogonal multiple access (NOMA) schemes have been recognized as a promising multiple access method for the fifth generation (5G) communication systems. In NOMA, multiple users can share the same physical channel, which allows for a substantial increase in capacity gains when comparing to conventional orthogonal multiple access (OMA) techniques. This paper considers the downlink transmission of NOMA schemes combined with single-carrier (SC) signals. We present a multi-antenna transmission technique that is compatible with highly efficient power amplifiers without requiring any pre-processing. Furthermore, a multi-user detection scheme based on iterative frequency-domain equalization (FDE) is presented. We show that besides the high power-efficiency of the transmission scheme, the system’s performance can be close to the matched filter bound (MFB).